Kebebasan Kehendak Manusia: Studi Kasus Penafsiran Bintu Shāṭī - Zaimul Asroor (Qur'an and Hadith Academic Society, 2019)
This study discusses the contribution of Arent Jan Wensinck in the science of takhrīj Hadith. Using the literature study method, this paper Arent Jan Wensinck contribution was in the science of takhrīj Hadith. Through searching the data contained in books, journals related to the topic, this study finds that Arent’s concept about the index of Hadith helps reviewer and users to find the intended hadith easier and faster.